Factors Influencing Narrative Transportation in Short Film Public Service Announcements on Social Media: An Integrated Structural Model - Jinxi Wei; Hasrul Hashim; Mohd Nor Shahizan Ali (e-Bangi Journal of social science and humanities, 2026)
Short film public service announcements (PSAs) are an increasingly prominent medium of public discourse on social media. However, research analysing how short film PSAs cultivate immersion in narrative experiences is still scarce. This research examines narrative transportation in the context of short film PSAs by bringing together features of the narrative, the audience, and the social media platform in a holistic model. A Solomon four-group experiment was conducted to expose participants to the short film PSA stimuli, and hypothesized relationships were examined with partial least squares structural equation modeling. These findings reveal that attention, identifiable characters, and the interaction of bullet screen among them significantly positively influence narrative transportation. By contrast, none of several factors typically linked with narrative persuasion, such as complete storyline, drama, verisimilitude, familiarity, transportability and likes, has any significant direct effect when tested in the integrated model. The results indicate that narrative transportation in short form public service storytelling is most strongly influenced by character-focused narrative cues, cognitive processing while viewing, and interactive platform affordances. The research extends the narrative transportation literature to the context of short film PSA on social media and offers practical recommendations for the development and distribution of digital public service communication.